Legal Policy of Implementation of Organizing Umrah Worship in Indonesia - Desnadya Anjani Putri (Global Legal Review, 2022)
Umrah is a worship for Muslims in the Holy Land of Mecca. The provision of umrah worship in Indonesia is stipulated in Law of Republic of Indonesia Number 8 of 2019 concerning the Implementation of Hajj and Umrah Worship and amended  under Law Number 11 of 2020 concerning Job Creation. The hope of being able to perform worship safely and comfortably does not always go well, because in fact there are still many problems that would have to be faced by umrah pilgrims. Referring to the Directory of Supreme Court's of Indonesia, every year there are cases registered in the Court regarding the Umrah Worship Travel Organizer, both in the civil lawsuit and criminal cases, this shows that there is still weak protection for umrah pilgrims. This research aims to explore and analyze regulations regarding the conduct of umrah worship in Indonesia, implementation of regulations, as well as the ideal arrangement of umrah worship in Indonesia. Methodology of this study is based on normative legal research which carried out several approaches such as statutory approach, case approach and comparative approach. In this paper, normative legal research is also supported by empirical research. The results of this study essencially show the potential problems in the Umrah worship arrangement that result in disadvantages for Umrah pilgrims who are not get they right to assigned to holy land Macca, the weak protection provided for Umrah worship shows potential problems in the umrah worship arrangement, therefore an alignment and amendment to the implementing regulations of the Umrah worship arrangement is required, the application of the obligation to provide insurance protection of departure certainty for all umrah pilgrims with any travel package is expected to provide protection and certainty of departure umrah.